Targeted information and limited attention - Andreas Hefti; Shuo Liu (University of Zurich, Department of Economics, 2016)
We study targeted information in a duopoly model with differentiated products, allowing for consumers with limited attention. The presence of inattentive consumers incentivizes firms to behave as if they were mass-advertisers, despite their ability to direct their messages precisely towards consumers with the strongest preferences. We show that the scope for targeting as an efficient marketing instrument can be severely reduced, for both firms and consumers, if the standard assumption of unbounded attention capacities is dropped. A central insight of our model is that limited attention may explain the recent evidence on increased ad-blocking, which has become a key concern to the entire advertising industry. Our main findings are robust to several variations, including price and salience competition as well as varying quality of the available marketing data.
Keywords: D43; L13; M37; 330; Targeting; limited attention; advertising avoidance; salience competition